Tribulus terrestris Protects against Male Reproductive Damage Induced by Cyclophosphamide in Mice - Pavin, Natasha Frasson (Oxid Med Cell Longev, 2018)
Tribulus terrestris (TT) has been considered as a potential stimulator of testosterone production, which has been related with steroidal saponins prevailing in this plant. Cyclophosphamide (CP) is the most commonly used anticancer and immunosuppressant drug, which causes several toxic effects, especially on the reproductive system. Patients who need to use CP therapy exhibit reduced fertility or infertility, which impacts both physically and emotionally on the decision to use this drug, especially among young men. We hypothesized that the treatment with TT dry extract would protect the male reproductive system against CP toxicity. Mice received dry extract of TT (11 mg/kg) or vehicle by gavage for 14 days. Saline or CP was injected intraperitoneally at a single dose (100 mg/kg) on the 14th day. Animals were euthanized 24 h after CP administration, and testes and epididymis were removed for biochemical and histopathological analysis and sperm evaluation. The dry extract of TT was evaluated by HPLC analysis and demonstrated the presence of protodioscin (1.48%, w/w). CP exposure increased lipid peroxidation, reactive species, and protein carbonylation and altered antioxidant enzymes (SOD, CAT, GPx, GST, and GR). Moreover, acute exposure to CP caused a reduction on 17 β-HSD activity, which may be related to the reduction in serum testosterone levels, histopathological changes observed in the testes, and the quality of the semen. The present study highlighted the role of TT dry extract to ameliorate the alterations induced by CP administration in mice testes, probably due to the presence of protodioscin.